Does routine carpal tunnel release during fixation of distal radius fractures improve outcomes?. (October 2017) - Medici, Antonio; Meccariello, Luigi; Rollo, Giuseppe; De Nigris, Giancarlo; Mccabe, Steven James; Grubor, Pedrag; Falzarano, Gabriele
Abstract: Objective: This case-control study was designed to test the hypothesis whether carpal tunnel release (CTR) during fixation of distal radius 23-C2 AO fractures improves outcomes. Methods: Thirty-five consecutive patients who sustained distal radius fractures of the dominant hand participated in this study. Patients were allocated into two groups: (a) The ORIF + CTR (16 patients (11 males and 5 females)); (b) the ORIF and NOT CTR 19 patients (12 males and 7 females). Patient assessment included visual analogic scale of pain (VAS), the subjective Mayo Wrist Score (MWS), electromyograms (EMG) at 3 month and 6 months from the day of injury and complications. All patients had the same physiotherapy treatment algorithm following surgery. Patient follow up took place at 1 month, 3, 6, and 12 months. Results: A the T12 month follow up point the VAS average was 0.8 (range 0–3) in ORIF + CTR group compared to 1.2 (range 0–3) in the ORIF and NOT CTR. The MWS average was 98.7 (range 95–100) in ORIF + CTR group versus 97.6 (range 95–100) in ORIF no CTR group. There was no statistical significance ( p > 0.5) between the two groups during the follow up period. Patients in the sixth month of ORIF + CTR had no suffering of the median nerve, while 31.58% of patients in ORIF and no CTR found to have carpal tunnel syndrome. Conclusions: Routine release of the transverse carpal ligament at the time of fracture fixation may reduce the incidence of postoperative median nerve dysfunction.